Highly porous of hydroxyethyl cellulose biocomposite scaffolds for tissue engineering - Farah Hanani, Zulkifli; Jahir Hussain, Fathima Shahitha; W. S., Wan Harun; M. M., Yusoff (Elsevier Ltd, 2019)
This study is focusing to develop a porous biocompatible scaffold using hydroxyethyl cellulose (HEC) and poly (vinyl alcohol) (PVA) with improved cellular adhesion profiles and stability. The combination of HEC and PVA were synthesized using freeze-drying technique and characterized using SEM, ATR-FTIR, TGA, DSC, and UTM. Pore size of HEC/PVA (2–40 μm) scaffolds showed diameter in a range of both pure HEC (2–20 μm) and PVA (14–70 μm). All scaffolds revealed high porosity above 85%. The water uptake of HEC was controlled by PVA cooperation in the polymer matrix. After 7 days, all blended scaffolds showed low degradation rate with the increased of PVA composition. The FTIR and TGA results explicit possible chemical interactions and mass loss of blended scaffolds, respectively. The Tg values of DSC curved in range of HEC and PVA represented the miscibility of HEC/PVA blend polymers. Higher Young's modulus was obtained with the increasing of HEC value. Cell-scaffolds interaction demonstrated that human fibroblast (hFB) cells adhered to polymer matrices with better cell proliferation observed after 7 days of cultivation. These results suggested that biocompatible of HEC/PVA scaffolds fabricated by freeze-drying method might be suitable for skin tissue engineering applications.